Analisis Konten Instagram @perpusnas.go.id dalam Menjelajahi Jenis Konten yang Diminati Oleh Followers - Liara Hayu Ningtias; Desky, Ahmed Fernanda (Tik Ilmeu : Jurnal Ilmu Perpustakaan dan Informasi, 2024)
Abstract This study aims to analyze the content preferences of followers of the Instagram account @perpusnas.go.id by evaluating their preferences and engagement with the presented content. The method used in this research is descriptive quantitative with an online survey approach. The instrument used is a questionnaire distributed to 100 active followers of the @perpusnas.go.id account, selected using purposive sampling techniques. Data were collected through Google Forms and analyzed descriptively to identify follower preferences and their level of engagement. The results show that educational content, library collections, and creative content are the most favored by followers. Although followers frequently view posts, the engagement level is relatively low, with 53% of respondents expressing a neutral attitude toward interaction with the content. Preference analysis reveals that informative and educational content aligns with the Literature Exhibits category in the theory of Zou et al., while promotional content and library activities reflect Library Showcasing. These findings suggest that increasing follower engagement can be achieved by enhancing visual quality and tailoring content to more specific follower interests. To improve engagement, the @perpusnas.go.id account needs to focus on enhancing the quality of visual design and presenting relevant and educational informative content in accordance with User Engagement theory. Keywords: content, Instagram, Library.